Genomic blueprint of population of Rajasthan based on autosomal STR markers - R. K. Kumawat; Pankaj Shrivastava; Divya Shrivastava; G. K. Mathur; Shivani Dixit (Taylor & Francis Group, 2020)
Aim: Genetic diversity and forensic efficacy of 20 autosomal STR genetic markers were investigated in a highly diverse population of Rajasthan, a state in north-western India. Subjects and methods: In this study, 317 blood samples from unrelated healthy individuals were directly amplified using the PowerPlex® 21 multiplex system (Promega). Amplified products were separated by capillary electrophoresis using a Genetic Analyser -3500 XL (Thermo Fisher Scientific). The data thus obtained was statistically analysed using population genetic software. Results: The studied population showed genetic affinity with the geographically close populations. The locus Penta-E was found to be the most polymorphic with a value of 0.90 in the studied population. The combined discrimination power (CPD) and combined power of exclusion (CPE) were observed as >0.999999999 and 0.999999997, respectively, for all the studied 20 autosomal STR loci. The combined probability of match (CPm) was 1.39 × 10−25 and combined paternity index (CPI) was 3.66 × 108 for all the studied loci. Conclusion: The results conclusively support the hypothesis that the studied autosomal STR loci are polymorphic in nature and, besides being useful in forensic applications they can also be applied in anthropological and other population genetic studies. This study supports the 'isolation-by-distance' model. Genetic data obtained from this study will enrich the population data bank.